Functional effects of extracellular vesicles altered by a per- and polyfluoroalkyl substance mixture: In vitro liver cytotoxicity and proteomic expression alterations - Celeste K. Carberry; Angie L. Mordant; Christine A. Mills; Hadley Hartwell; Victoria F. Carberry; Lauren Simendinger; Elise Hickman; Laura E. Herring; Julia E. Rager (PLoS ONE, 2026)
Per- and polyfluoroalkyl substances (PFAS) have become a focal point in public health research due to their widespread use and persistence, leading to global environmental and human exposure. Accumulating evidence associates PFAS with hepatotoxicity, disrupted liver function, and progression of liver diseases. Simultaneously, extracellular vesicles (EVs) have emerged as key mediators of intercellular communication and potential modulators of exposure-induced disease. Prior studies have revealed that PFAS exposure alters EV release and content, implicating EVs in PFAS-induced liver toxicity. This study evaluated the functional effects of EVs from HepG2 liver cells exposed to a PFAS mixture on the biology of separate recipient HepG2 cells. We hypothesized that EVs from PFAS-treated cells are biologically active and modulate protein expression related to liver diseases and cancer. Parent HepG2 cells were exposed to an equimolar PFAS mixture (PFOS, PFOA, PFHxA), and EVs were isolated and used to treat separate recipient HepG2 cells. Changes in cellular viability and proteomic profiles were measured and further interpreted using pathway and miRNA target analyses. Results demonstrated that EVs derived from PFAS-treated liver cells decrease cell viability. Furthermore, EVs released from PFAS-treated cells cause unique protein expression changes in separate cells, including numerous proteins previously associated with hepatic cancer, non-alcoholic fatty liver disease, and other hepatic diseases. Proteomic pathway analysis further supported this finding, highlighting possible pathways perturbed by EVs derived from PFAS-treated HepG2 cells, including oxidative stress, immune response, and metabolism. These findings highlight a novel mechanism of PFAS toxicity mediated by EVs, underscoring a potential functional role in liver disease progression and potential as targets for mitigating PFAS-induced health effects.